Long-Term Outcomes of Patients with Stent Tips Embedded into Internal Carotid Artery Branches during Aneurysm Coiling - Ban, S.P.; Kwon, O.-K.; Lee, S.U.; Bang, J.S.; Oh, C.W.; Jeong, H.J.; Cho, M.J.; Jeong, E.-A.; Kim, T. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: During stent-assisted coiling of ICA aneurysms, stent tips are sometimes unintentionally embedded into ICA branches. Stent tips can be visualized because they have radiopaque markers. Concerns regarding stent tip misplacement include risks of artery perforation and occlusion. The aim of this study was to evaluate the long-term outcomes of ICA branches with embedded stent tips.MATERIALS AND METHODS: ICA branches with embedded stent tips were identified among 35 patients with unruptured ICA aneurysms treated with stent-assisted coiling between November 2003 and November 2014. Patient clinical and angiographic outcomes associated with the embedded stent tip were analyzed.RESULTS: Most of the 35 studied aneurysms were paraclinoid ICA aneurysms (n = 30). The most commonly involved ICA branch was the posterior communicating artery (26 patients, 74.3%), followed by the anterior choroidal artery (8 patients, 22.9%) and ophthalmic artery (1 patient, 2.9%). During the follow-up period (38.6 ± 17.9 months), no new neurologic deficits developed. Neither hemorrhagic nor thromboembolic events occurred. Angiography was performed during the final follow-up evaluation at a mean of 32.7 ± 18.0 months, and all ICA branches with embedded stent tips showed patent blood flow without severe luminal narrowing.CONCLUSIONS: In our experience, placement of a stent tip into ICA branches during stent-assisted coiling was not associated with any major adverse events.AchoAanterior choroidal arteryOphAophthalmic arteryPcomAposterior communicating arterySACstent-assisted coiling